Atrial fibrillation and age synergistically increase clotting potential and promote atrial structural remodeling in goats. (19th May 2022) - D' Alessandro, E; Scaf, B; Sobota, V; Van Hunnik, A; Kuiper, M; Winters, J; Van Oerle, R; Spronk, HMH; Van Nieuwenhoven, FA; Ten Cate, H; Verheule, S; Schotten, U
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Netherlands Heart Foundation, European Union Background: Age is a risk factor for atrial fibrillation (AF) as well as for stroke in patients with AF. However, the effect of ageing on AF mechanisms and on coagulation activity is not well understood. Purpose: To evaluate the effect of age and AF on coagulation activity, AF characteristics, and atrial structural remodeling. Methods: Four groups of female goats were investigated: Young sham (Y-Sh: sinus rhythm, <3 years old, n=9), Young AF (Y-AF: 4 weeks of AF, <3 years old, n=7), Old sham (O-Sh: sinus rhythm, >8 years old, n=6), and Old AF (O-AF, 4 weeks of AF, >8 years old, n=8). Groups were matched for body weight. AF was maintained using implantable pacemakers in both AF groups. Clotting potential, expressed as the ability of activated plasma to generate thrombin, was measured using tissue factor-induced thrombin generation assays at baseline and 4 weeks (final). A terminal experiment was performed with atrial contact mapping to study electrophysiological AF properties and to collect atrial tissue for histological analysis. Results: Thrombin generation analysis showed that 4 weeks of AF induced a significant increase in clotting potential in old, but not in young goats. AF complexity and hemodynamics were not affected by age alone. AF, however, significantly increased the right atrial pressure in old (O-Sh: 6.4±1.9 vs. O-AF: 11.4±3.1 mmHg, p=0.02), but not in young goats. AF induced atrial myocyte hypertrophy and left atrial epicardial endomysial fibrosis in old goats, while this was not the case in young goats. Conclusion: Four weeks of AF and advanced age synergistically enhanced coagulation potential and promoted atrial structural remodeling in goats. Complexity of atrial conduction was affected by AF, but not by age.